Da sala de aula para o instagram: os studygrammers e o ensino-aprendizagem em ciências e biologia - COSTA, José Maria Martins (Universidade Federal de Mato Grosso, 2022)
In post-modernity, information and knowledge are produced and disseminated through technologies, especially the internet and digital media. Students and teachers have in their hands resources that allow open access to knowledge, which inspires changes and constant inventions in the field of education. In the Internet social networks, profiles are being created to explain materials and/or study routines, in order to share experiences, inspire others and disseminate and discuss relevant topics, known as Studygams. In this sense, the objective of this study was to identify trends and contributions of Studygrams to the teaching and learning of Science and Biology, in the view of a panel of Studygrammers who produce and publish content related to Biological Sciences in Brazil. The work was developed from a qualitative approach, with elements of netnographic research such as participant observation and online fieldwork. The results showed that Studygrams have the potential to explore and develop skills and abilities in both those who post and those who access the content. It is understood that this new practice of teaching and learning in informal spaces has aroused attitudes of entrepreneurship, autonomy, organization, interaction and creativity, which allow the fixation of contents, interdisciplinarity, contextualization and training for citizenship.